Interlayer behavior investigation of box profile shear connectors in steel-concrete-steel sandwich structures - Khatibi, Seyed Hashem; Ghohani Arab, Hamed; Miri, Mahmoud (Structures (Oxford), 2022)
The present study introduces box profile (BP) shear connectors for steel-concrete-steel sandwich composite structures. The shear connectors were joined to steel faceplates using slot and fillet welding. The advantages of this shear connector include unlimited thickness, easy application, high strength, and low cost compared to other available shear connectors. A total of eight experimental specimens were fabricated to evaluate the interlayer shear behavior of BP shear connectors. The effects of geometric parameters, including the BP thickness, BP width, concrete thickness, and BP configuration, on the shear behavior of the BP shear connectors were studied. The results of experiments and comparison with other shear connectors show that BP shear connectors have improved the composite behavior and interlayer shear strength. Also, the effect of geometrical parameters was analyzed on the shear strength. The BP shear connector is dependent on its width. A 20-mm rise in the width of the BP connector increased the ultimate strength and energy absorption by 76% and 41%, respectively. The use of BP shear connectors in a V-WEB configuration reduced ductility by 52% (from 501.4 to 239 kN.mm) and initial strength by 43% (from 192 to 109 kN). Therefore, V-WEB BP shear connectors are not recommended. Then, a model was offered to predict the load-slip behavior of BP shear connectors and was compared with the relations of previous researchers. Finally, the proposed shear connector was compared with different available shear connectors in terms of strength and load-slip behavior. It can be concluded that the BP shear connector had higher stiffness and ultimate strength than other shear connectors, e.g., stud bolt, bi-steel, J-hook, CSC, and headed stud shear connectors.